Variation in problem-solving success amongst children with and without a family history of ADHD - Hendry, Alexandra; Konke, Linn Andersson; Jones, Emily J.H.; Charman, Tony; Falck-Ytter, Terje (Center for Open Science, 2024)
BackgroundAttention-Deficit/Hyperactivity Disorder (ADHD) is linked to strengths in creative problem-solving amongst school-aged children and adults. In contrast, autism (which frequently co-occurs with ADHD) is associated with lower generativity, and perseverative responses during problem-solving. Little is known about how ADHD and autism traits – or broader heritable autism and ADHD phenotypes – associate with problem-solving skills in early childhood.Methods129 UK 2- and 3-year-olds (exploratory dataset) and 74 Swedish 3-year-olds (confirmatory dataset) with and without a family history (FH) of ADHD and autism, completed a problem-solving task. Parents reported on their 3-year-olds’ ADHD and autism traits using the Child Behavior Checklist and Social Responsiveness Scale-2. FH group differences in problem-solving performance (success, generativity, perseveration, persistence) were tested using ANOVA in the exploratory dataset. A pre-registered t-test followed up FH-ADHD effects on problem-solving success in the confirmatory dataset. Linear regressions of problem-solving success on autism/ADHD traits were run in both samples.ResultsCompared with peers with no FH-ADHD, children with FH-ADHD showed higher problem-solving success at 2 (partial ω2=.106) and 3 years (partial ω2=.045) in the exploratory dataset. The hypothesized FH-ADHD effect was of a consistent direction and magnitude in the confirmatory dataset but success scores were only significantly higher for children with FH-ADHD when compared with children with no FH-ADHD-or-autism (gs =.977). Parent-reported ADHD (but not autism) traits were positively associated with problem-solving performance in the exploratory (β=.212, p=.031) and combined samples (β=.173, p=.024). Effects were of a consistent direction and magnitude but not significant in the confirmatory sample alone (β=.201, p=.103). ConclusionsConsidering a child’s family history alongside their neurodivergent traits may help to identify their likely strengths, and how to access them: Children with ADHD traits and/or a family history of ADHD are likely to have an aptitude for generative problem-solving when presented with highly-motivating, ecologically-valid challenges.
Keywords: 10. No inequality